2022
DOI: 10.3390/s22197404
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Wheelchair Related Shoulder Loading Activities from Wearable Sensor Data: A Machine Learning Approach

Abstract: Shoulder problems (pain and pathology) are highly prevalent in manual wheelchair users with spinal cord injury. These problems lead to limitations in activities of daily life (ADL), labor- and leisure participation, and increase the health care costs. Shoulder problems are often associated with the long-term reliance on the upper limbs, and the accompanying “shoulder load”. To make an estimation of daily shoulder load, it is crucial to know which ADL are performed and how these are executed in the free-living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
(93 reference statements)
2
4
0
Order By: Relevance
“…Device D, capturing acceleration, heart rate (HR), and respiratory rate (RR) data on the chest, was deemed irrelevant for ADL classification in manual wheelchair users using the proposed methodology and features. This aligns with prior studies that solely utilized kinematic data for activity classification in manual wheelchair users, thereby excluding non-kinematic modalities like HR and RR [10], [11]. In [10] it was similarly demonstrated that non-kinematic data in the form of muscle activity do not aid in ADLs classification.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Device D, capturing acceleration, heart rate (HR), and respiratory rate (RR) data on the chest, was deemed irrelevant for ADL classification in manual wheelchair users using the proposed methodology and features. This aligns with prior studies that solely utilized kinematic data for activity classification in manual wheelchair users, thereby excluding non-kinematic modalities like HR and RR [10], [11]. In [10] it was similarly demonstrated that non-kinematic data in the form of muscle activity do not aid in ADLs classification.…”
Section: Resultssupporting
confidence: 81%
“…This aligns with prior studies that solely utilized kinematic data for activity classification in manual wheelchair users, thereby excluding non-kinematic modalities like HR and RR [10], [11]. In [10] it was similarly demonstrated that non-kinematic data in the form of muscle activity do not aid in ADLs classification. Additionally, device A1 (pressure mat -backrest), did not enhance the performance.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…To evaluate sensor data, especially in a sparse measurement setup, machine learning techniques are necessary [ 20 , 21 ]. In recent years, IMU and machine learning techniques, including artificial neural networks (ANN), have been successfully applied in both classification and prediction tasks in biomechanical settings [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Traditional machine learning algorithms such as Random Forest, Support Vector Machine, etc., require time-intensive feature engineering and manual feature extraction.…”
Section: Introductionmentioning
confidence: 99%